The ethanol extract of Excoecaria cochinchinensis Lour. leaves inhibits cell migration and arrests cell cylce in gastric cancer cell MKN45 - Hung, Nguyen Phu; Huong, Le Thi Thanh (Vietnam Journal of Biotechnology, 2021)
According to Globocan 2020, stomach cancer is the 5th most common cancer in the world. Vietnam belongs to the group of 20 countries with the highest rate of stomach cancer in the world with 17906 new cases and 14615 deaths in 2020. Natural medicinal products are gaining increasing popularity and use worldwide as complementary alternative therapies. Excoecaria cochinchinensis Lour. is an herb widely distributed in many Southeast Asian countries and China. Current understanding of the effects of E. cochinchinensis on cancer cells is limited. In this study, we collected ethanol extract from the leaves of E. cochinchinensis and assessed its impacts on MKN45 gastric cancer cells. Our study showed that the ethanol extract of the E. cochinchinensis leaves was able to strongly inhibit the proliferation of MKN45 gastric cancer cells, from 40% to 80% compared to the control, with an IC50 value of 0,07 mg/mL. On the other hand, the leaf extract also reduced the level of cell migration from 20% to 70% compared to the control in a concentration-dependent manner. Flow cytometry analysis also showed that the leaf extract arrested the cell cycle in G2/M phase (P < 0,05). Overall, the results showed that the leaf extract of Excoecaria cochinchinensis had the potential to inhibit gastric cancer cells.